2014
DOI: 10.1111/gcbb.12160
|View full text |Cite
|
Sign up to set email alerts
|

The economics and greenhouse gas balance of land conversion to Jatropha: the case of Tanzania

Abstract: Due to higher oil prices, abundance of labor and suitable land and its stable political climate, Tanzania attracted many investments in Jatropha. Although several studies on Jatropha's economic potential are available, its true economics are still uncertain. This paper aims to add to the growing body of knowledge on the socio-economic performance of the Jatropha system by (i) studying the economic potential (net present value -NPV) of the current most prevailing Jatropha system for Tanzanian farmers and its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Variations in LCA methodology or scope are equivalent to asking a different 'LCA question' (Adams et al, 2013) and can result in different GHG performance estimates for a given bioenergy system Thornley et al, 2015). One significant source of methodological variation is in the assumptions around business-as-usual counterfactual scenarios for land use in LCA (Thomas et al, 2009;Achten et al, 2015). For example, significant GHG savings were achieved from bioenergy heat pathways utilizing agricultural residues and perennial bioenergy crops, but savings were extremely sensitive to the counterfactual land-use scenario (Welfle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in LCA methodology or scope are equivalent to asking a different 'LCA question' (Adams et al, 2013) and can result in different GHG performance estimates for a given bioenergy system Thornley et al, 2015). One significant source of methodological variation is in the assumptions around business-as-usual counterfactual scenarios for land use in LCA (Thomas et al, 2009;Achten et al, 2015). For example, significant GHG savings were achieved from bioenergy heat pathways utilizing agricultural residues and perennial bioenergy crops, but savings were extremely sensitive to the counterfactual land-use scenario (Welfle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first comparative study of the carbon impacts associated with the two main feedstocks (Jatropha and sugarcane) and dominant modes of production (smallholder and plantations) adopted in southern Africa. While there are some studies about the effects of Jatropha on carbon stocks in Africa [18][19][20][21][22], there is a critical lack of empirical research on sugarcane as identified in a recent meta-analysis [1]. To the authors' best knowledge, the only study that has considered the carbon impacts of land use change due to sugarcane ethanol production in Africa (Malawi) has made substantial assumptions [23].…”
Section: Introductionmentioning
confidence: 99%